2010
DOI: 10.1016/j.worlddev.2009.11.003
|View full text |Cite
|
Sign up to set email alerts
|

One Size Fits All? Decentralization, Corruption, and the Monitoring of Bureaucrats

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 150 publications
(93 citation statements)
references
References 36 publications
(46 reference statements)
6
81
0
6
Order By: Relevance
“…Lessmann and Markwardt (2010) study the effect of decentralization on corruption, which depends on the monitoring possibilities of bureaucrats (as reflected by the degree of press freedom). However, both studies do not consider the level of democracy.…”
Section: Freedom Of the Press And Corruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lessmann and Markwardt (2010) study the effect of decentralization on corruption, which depends on the monitoring possibilities of bureaucrats (as reflected by the degree of press freedom). However, both studies do not consider the level of democracy.…”
Section: Freedom Of the Press And Corruptionmentioning
confidence: 99%
“…Treisman (2000), Chowdhury (2004), Brunetti and Weder (2003)]. However, recent studies on the causes of corruption have demonstrated that the estimation of unconditional effects may lead to misleading policy conclusions, since the corruption alleviating effect of single corruption determinants may depend on others [see Saha et al (2009) and Lessmann and Markwardt (2010)]. We argue based on the theoretical literature that both instruments -democratic elections and press freedom -are complements rather than substitutes in reducing corruption.…”
Section: Introductionmentioning
confidence: 97%
“…Standard instruments for decentralization as used in the literature are the size of a country or the degree of ethnolinguistic fractionalization [see e.g. Wasylenko (1987), Arikan (2004), or Lessmann and Markwardt (2010)]. However, these instruments are not applicable in my context since they are linked to regional inequality through other channels than decentralization.…”
Section: Endogeneitymentioning
confidence: 99%
“…In this way, corruption is held constant and considered a country feature that only changes very gradually over time, and instead we focus on 26 Indeed, Treisman (2000) provides robust evidence that federal states are more corrupt. 27 Focusing on a broad cross-section of 64 countries over the period 1980-2000, Lessmann and Markwardt (2010) provide evidence that a free press is necessary for fiscal decentralization to reduce the extent of corruption.…”
Section: Within-country Effects: An Alternative Empirical Approachmentioning
confidence: 99%